How mobile phones can improve nutrition among pastoral communities: Panel data evidence from Northern Kenya - Martin C. Parlasca; Oliver Mußhoff; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
The digital revolution and the ongoing dissemination of mobile phones carry several prospects for smallholder farmers in Sub-Saharan Africa. Food insecurity remains a major issue among African smallholders. Mobile phones could potentially facilitate access to food markets and thus improve food security and nutrition, but research on such types of effects remains scarce. In this study we analyze whether mobile phones improve dietary quality of pastoralists in Northern Kenya. We use six rounds of household panel data covering the period between 2009 and 2015. During this period, mobile phone ownership in the sample increased from less than 30% to more than 70%. Regression models with household fixed effects allow robust estimation while reducing potential issues of unobserved heterogeneity. The estimates show that mobile phone adoption has increased dietary diversity. The effect size increases with the frequency of mobile phone use. We also examine the underlying mechanisms. Mobile phones improve dietary diversity mainly through better access to purchased foods. These results encourage the promotion of mobile phone technologies as a valuable tool for nutritional improvements, especially in rural settings with poor access to food markets.
Keywords: I15; O12; O33; 330; mobile phones; dietary diversity; nutrition; pastoralism; Africa; Northern Kenya